EMPLOYEE REWARDS AND MOTIVATION IN PORTUGUESE MERCIES - Santos, Vasco (2022)
Goal – This study aims to investigate the influence of rewards on work motivation in Portuguese mercies. Method - To achieve our goal a quantitative descriptive study was carried out based on an online survey. A convenience sample of 132 collaborators of the Portuguese mercies was used. Results - The results show that intrinsic task and knowledge rewards as well as extrinsic social rewards have a positive impact on autonomous motivation. Discussion - There was no significant evidence regarding the impact of intrinsic and extrinsic rewards on controlled motivation. Having found that perceptions of intrinsic rewards are more positive than those of extrinsic rewards; and, that employees have higher levels of autonomous motivation than controlled motivation. Conclusion - The present study allowed us to assess which rewards had the greatest impact on mercies employees’ motivation, contributing to the understanding of the most appropriate instruments for an effective management of human resources motivation in these institutions.